Gladys Black letter to Nicholas S. Halmi regarding fall migration, 1976 - Black, Gladyset al (1976)
Fall migration report contributed by Gladys Black in a letter to Nicholas S. Halmi, November 23, 1976. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1976. Epson - sheet feed/flatbed